DISASTER RESILIENT VILLAGES AS A LEVEL FOR TSUNAMI PREPAREDNESS - Paulus Punjung Widodo; Vitria Wuri Handayani; Dedi Kurniawan (Airlangga Development Journal, 2023)
Indonesia's geographical location which is located between three plates makes Indonesia a country that is prone to disasters, one of which is the threat of a tsunami disaster. Tulungagung, which is located on the southern coast of the island of Java, is one of the areas prone to tsunamis. The new disaster management paradigm is focused on efforts to reduce disaster risk. Strengthening village capacity by creating a Disaster Resilient Village (Destana), is one of the effective efforts to reduce disaster risk. The purpose of this study was to provide an overview of the readiness of the Besole hamlet, Tulungagung Regency. The research method used is descriptive research by collecting the results of in-depth interviews with the Destana community activists in Besole hamlet, Tulungagung Regency. The results obtained from this study were participation, the Besole Village community was involved from the beginning, namely from the start of preparation for the establishment of the Destana by conducting disaster risk studies, making evacuation route maps, determining gathering points, as well as installing and maintaining early warning system tools. For the role of participation, there is no sustainability in the community, readiness is good and management is good. Keywords: Disaster Resillent Village, Tsunami